Sooty bark disease of maples: the risk for hypersensitivity pneumonitis by fungal spores not only for woodman - Markus Braun; Doris Klingelhöfer; David A. Groneberg (Journal of Occupational Medicine and Toxicology, 2021)
Abstract In the middle of the twentieth century, the from North America sooty bark disease (SBD) of maples was first discovered in England and has spread in the last decades in Central Europe, in particular. The trigger of SBD is the mould fungus Cryptostroma (C.) corticale. The most common infested maple is the sycamore, Acer pseudoplatanus, a common tree in woods and parks. The disease is characterised by peeling of the outer layer of the bark and brownish-black spores under the peeled off bark. These spores can cause maple bark disease (MBD) in humans, a hypersensitivity pneumonitis (HP) with similar symptoms like COPD, allergic asthma, influenza or flu-like infections and interstitial pneumonia. Persons who have intensive respectively occupational contact with infested trees or wood, e.g., woodman, foresters, sawyers or paper mill workers, are at risk in particular. Since C. corticale favours hot summers and host trees weakened by drought, SBD will increasingly spread in the future due to ongoing climate change. Consequently, the risk of developing MBD will increase, too. As with all HPs, e.g., farmer’s lung and pigeon breeder’s disease, the diagnosis of MBD is intricate because it has no clear distinguishing characteristics compared to other interstitial lung diseases. Therefore, the establishment of consistent diagnosis guidelines is required. For correct diagnosis and successful therapy, multidisciplinary expertise including pulmonologists, radiologists, pathologists and occupational physicians is recommended. If MBD is diagnosed in time, the removal of the triggering fungus or the infested maple wood leads to complete recovery in most cases. Chronic HP can lead to lung fibrosis and a total loss of lung function culminating in death. HP and, thus, MBD, is a disease with a very high occupational amount. To avoid contact with spores of C. corticale, persons working on infested wood or trees have to wear personal protective equipment. To protect the public, areas with infested maples have to be cordoned off, and the trees should be removed. This is also for impeding further spreading of the spores.